Analisis Komunikasi Pemasaran Terpadu dan Kualitas Pelayanan terhadap Citra Perguruan Tinggi pada Keputusan Menjadi Mahasiswa S1 Ilmu Komunikasi Stikom Bandung - Rachmat Taufik (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2018)
This study aims to reveal the integrated marketing communication, service quality, image-making college and became a student STIKOM Bandung. In addition this study also aims to determine how much influence the integrated marketing communications and service quality to the image of the university in Bandung STIKOM and determine how much influence the image of the college to the decision a student STIKOM Bandung. Locus research conducted in Bandung STIKOM through random sampling method with iterative model approach. The number of samples processed as many as 116 respondents, out of a population of 408 active students STIKOM Bandung, the academic year 2012/2013 until 2016/2017 academic year. The data collection techniques done through questionnaires, interviews and direct observation. In this study the variables studied was integrated marketing communications and service quality, which serves as the independent variables, as well as the image of the university and the decision to become a student as a dependent variable. As for the hypothesis test, path analysis and multiple regression analysis method to test the hypothesis of F test and t test at level α = 0.05. SPSS. The results of data analysis and processing, concluded as follows: 1) integrated marketing communications partial effect on the image of the college. 2) The service quality is partially affected the image of the college. 3) integrated marketing communications and quality of service simultaneously affect the image of higher education, and 4) The image of the college is partially an effect on a student's decision of STIKOM Bandung.